The Impact Of Sports Activities On Quality Of Life Of Persons With A Spinal Cord Injury - Kljajić Dragana; Eminović Fadilj; Dopsaj Milivoj; Pavlović Dragan; Arsić Sladjana; Otašević Jadranka (Sciendo, 2016)
Studying the quality of life of people with a spinal cord injury is of great importance as it allows the monitoring of both functioning and adaptation to disability. The aim of this study was to determine the difference between persons with a spinal cord injury involved in sports activities and those not involved in sports activities in relation to their quality of life and the presence of secondary health conditions (pressure ulcers, urinary infections, muscle spasms, osteoporosis, pain, kidney problems-infections, calculosis and poor circulation).